Molecular Mechanisms of Protein Aggregation in ALS-FTD: Focus on TDP-43 and Cellular Protective Responses - Enza Maria Verde; Valentina Secco; Andrea Ghezzi; Jessica Mandrioli; Serena Carra (Cells)
Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Dementia (FTD) are two neurodegenerative disorders that share common genes and pathomechanisms and are referred to as the ALS-FTD spectrum. A hallmark of ALS-FTD pathology is the abnormal aggregation of proteins, including Cu/Zn superoxide dismutase (SOD1), transactive response DNA-binding protein 43 (TDP-43), fused in sarcoma/translocated in liposarcoma (FUS/TLS), and dipeptide repeat proteins resulting from C9orf72 hexanucleotide expansions. Genetic mutations linked to ALS-FTD disrupt protein stability, phase separation, and interaction networks, promoting misfolding and insolubility. This review explores the molecular mechanisms underlying protein aggregation in ALS-FTD, with a particular focus on TDP-43, as it represents the main aggregated species inside pathological inclusions and can also aggregate in its wild-type form. Moreover, this review describes the protective mechanisms activated by the cells to prevent protein aggregation, including molecular chaperones and post-translational modifications (PTMs). Understanding these regulatory pathways could offer new insights into targeted interventions aimed at mitigating cell toxicity and restoring cellular function.